The Privatization Origins of Political Corporations: Evidence from the Pinochet Regime (2020)
We show that the sale of state-owned firms in dictatorships can help political corporations to emerge and persist over time. Using new data, we characterize Pinochet's privatizations in Chile and find that some firms were sold underpriced to politically connected buyers. These newly private firms benefited financially from the Pinochet regime. Once democracy arrived, they formed connections with the new government, financed political campaigns, and were more likely to appear in the Panama Papers. These findings reveal how dictatorships can influence young democracies using privatization reforms. © The Economic History Association 2020.